Practical, corrected Kirkpatrick-Baez telescope for x-ray astronomy - Longcope, Dana; Acton, Loren; Kankelborg, Charles (Applied optics. Optical technology and biomedical optics, 2019)
Kirkpatrick-Baez (K-B) optics offer a means of imaging soft x-rays with modest resolution and a multi-arc-minute field of view at a cost far below the conventional Wolter design. Such a low-cost system could be useful for dedicated, long-time-line observation of astronomical x-ray sources from orbit. A K-B telescope consists of crossed arrays of parabolic mirrors at grazing incidence. The classic K-B telescope is subject to significant aberration arising from the interplay between the focusing of the fore and aft mirror arrays. We demonstrate here a corrected K-B prescription with aberrations reduced by an order of magnitude. We show, furthermore, that it is possible to construct such a system by constraining flat "slats" of commercially available glass in precision-milled grooves. The slats deform into shapes that adequately approximate the optimal figures, thereby yielding focusing better than the best version of the classic K-B telescope. The result is a new approach that greatly simplifies the task of achieving both useful resolution and high effective area for x-ray astronomy applications.